2012
DOI: 10.1016/j.bandl.2011.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Co-localisation of abnormal brain structure and function in specific language impairment

Abstract: Graphical abstractHighlights► Compared brain structure and function in SLI, unaffected siblings, and typical peers. ► More grey matter in SLI in the left inferior frontal cortex. ► Less grey matter in SLI in the right caudate nucleus and superior temporal cortex bilaterally. ► Functional activation was examined with an auditory covert naming task. ► Functionally, SLI had reduced activation of the left inferior frontal cortex and the superior temporal cortex bilaterally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
157
3
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(186 citation statements)
references
References 58 publications
(61 reference statements)
23
157
3
3
Order By: Relevance
“…This finding would be in line with previously reported motor (speech) disorders in galactosemia (Potter, 2011;Potter et al, 2013;Rubio-Agusti et al, 2013;Shriberg et al, 2011). Hypoactivity of the posterior STG and PT has been observed in patients with specific language impairment (SLI) (Badcock et al, 2012) and CAS as well (Liegeois et al, 2003). Weaker connectivity in patients between IFG and the right PT, and bilateral superior parietal regions supports this claim, suggesting suboptimal communication between frontal areas associated with overall language planning (IFG) and temporal and parietal sensory-motor integration (PT, superior parietal region).…”
Section: Discussionsupporting
confidence: 89%
“…This finding would be in line with previously reported motor (speech) disorders in galactosemia (Potter, 2011;Potter et al, 2013;Rubio-Agusti et al, 2013;Shriberg et al, 2011). Hypoactivity of the posterior STG and PT has been observed in patients with specific language impairment (SLI) (Badcock et al, 2012) and CAS as well (Liegeois et al, 2003). Weaker connectivity in patients between IFG and the right PT, and bilateral superior parietal regions supports this claim, suggesting suboptimal communication between frontal areas associated with overall language planning (IFG) and temporal and parietal sensory-motor integration (PT, superior parietal region).…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, dyslexic readers have been reported to not show the typical leftward asymmetry of the planum temporale (e.g., Hynd, SemrudClikeman, Lorys, Novey, & Eliopulos, 1990;Larsen, Høien, Lundberg, & Odegaard, 1990), although reports have been inconsistent (for a review, see Heim & Keil, 2004). Structural abnormalities of the planum temporale and surrounding areas have further been associated with other developmental speech and language disorders like specific language impairment (e.g., Badcock, Bishop, Hardiman, Barry, & Watkins, 2012) or stuttering (e.g., Foundas et al, 2004). We therefore interpret the significant positive relationship between left superior temporal gray matter volume and subsequent changes in reading proficiency as evidence for preexisting neurostructural differences, which might be associated with differences in general linguistic abilities.…”
Section: Discussionmentioning
confidence: 99%
“…It is highly heritable, and so far several risk genes and copy-number variants have been identified (Deriziotis & Fisher, 2013;Simpson et al, 2015). Neuroimaging studies of individuals with SLI have revealed structural and functional differences in left frontal and temporal regions associated with language as well as in basal ganglia structures (Badcock, Bishop, Hardiman, Barry, & Watkins, 2012;van der Lely & Pinker, 2014). Despite how common the disorder is, there has been relatively little systematic research on the neural systems that underlie language impairment in SLI, and most published studies include small sample sizes and different methodologies.…”
Section: Slimentioning
confidence: 99%